Interior view of the Garbhagriha of the Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of the garbhagriha (sanctum sanctorum) interior of the Someshwar Mahadev Temple. The walls and ceiling are plain. Presently, the object of worship in the garbhagriha is a Shiva linga (aniconic representation of Shiva), which appears to have been kept here at a later date. The back wall of the garbhagriha has a low-relief empty niche.